Avaliação do potencial antitumoral e antiangiogênico de novos análogos ftalimídicos da talidomida - Costa, Patricia Marçal da (2011)
The thalidomide was previously used to relieve gastric discomforts during pregnancy, and currently it is used for cancer treatment and inflammatory illnesses. Various phthalimides analogues of thalidomide have been researched for its antiangiogenic and immunemodulatory activity. In previous studies, these analogues showed absence of immunesuppressor activity. In this context, this work initially determined the cytotoxic activity of eight phthalimides analogues of thalidomide, in a series of cancer cell lines and of isolated peripheral mononuclear blood cells (PMBC) after 72h of incubation. None of compounds revealed cytotoxic activity in vitro in cancer cell lines and hemolytic activity towards of PBMC. They also showed no potential damage to the DNA strand, therefore they were not considered genotoxic towards human PMBC. The antitumor effect (in vivo) of thalidomide along with eight analogues was analyzed in mice transplanted with the Sarcoma 180 tumor and treated in a dose of 50mg/Kg/7 days, i.p. The inhibition of the tumor growth was only significant in mice treated with thalidomide (53.5%) and the analogues SC-10 and SC-11 (67.9% and 67.4%, respectively), p< 0,05. The histopathological analysis of the animals’ organs showed mainly that thalidomide and its analogues cause moderate toxic effects, mostly in the liver, but these can be considered reversible. The studies concerning the mechanism of action were deepened using isolated cells from the Sarcoma 180, after 72 hours of incubation, in the doses of 10, 50 and 100µg/mL. The following flow cytometry assays were carried out: 1- Evaluation of the membrane integrity, cellular viability and concentration of cells; 2- Determination of the nuclear DNA content. All the compounds led to the loss of membrane cell integrity and it was found internucleossomal DNA fragmentation in the higher concentrations, indicating the presence of cells with late stage apoptotic characteristics or in the process of secondary necrosis. The evaluation of the antiangiogenic potential, with the Wound Healing assay revealed that for the endothelial cell line (HUVEC) the analogue SC-10 caused a greater inhibition (65.28% ± 1,58), whereas in the tumor cell line the highest effect was of the analogue SC-11 (98.51% ± 0,25). The thalidomide was not capable of reducing cellular migration in none of the tested cell lines. In the chorioallantoic membrane assay (CAM), an antiangiogenic potential was observed with analogous SC-10 and SC-11 (5mg/mL), where there was an inhibition in the number of vessels (12, 88% ± 2,3 and 14.81% ± 3,3), the area of neovascularization (13.14% ± 1,7 and 14.26% ± 1,7) and the total length of vessels in mm2 (9.19% ± 1,5 and 9.86% ± 1,9). The thalidomide was not capable of inhibiting embryonic vascularization. The antitumor effect (in alive) of thalidomide and the analogues SC-10 and SC-11 was analyzed in mice transplanted with the Sarcoma 180 tumor, treated with the dose of 50mg/Kg/10 days, i.p. It was observed inhibition of the tumor growth in the thalidomide treatment (56,6%) and for analogues SC-10 and SC-11 (48.2% and 41.3%, respectively), p< 0,05. The immunostaining of intratumor endothelial cells with CD-31, showed, in the form of microvascular density, reduction in the groups treated with analogues SC-10 and SC-11 (64.59% and 46.51%), but not in the groups treated with thalidomide. These results, along with previous studies of immunemodulation suggest antitumor and antiangiogenic immunity, T cells dependent, for the phthalimides analogues.